A reader in Latina feminist theology : religion and justice - Aquino, María Pilar; Machado, Daisy L.; Rodriguez, Jeanette, 1954- (University of Texas Press, 2002)
With twelve original essays by emerging and established Latina feminist theologians, this volume adds the perspectives, realities, struggles, and spiritualities of U.S. Latinas to the larger feminist theological discourse. The editors have gathered writings from both Roman Catholics and Protestants and from various Latino/a communities. The writers address a wide array of theological concerns: popular religion, denominational presence and attraction, methodology, lived experience, analysis of nationhood, and interpretations of life lived on a border that is not only geographic but also racial, gendered, linguistic, and religious.